Klf6 protects β-cells against insulin resistance-induced dedifferentiation - Christopher Dumayne; David Tarussio; Ana Rodriguez Sanchez-Archidona; Alexandre Picard; Davide Basco; Xavier Pascal Berney; Mark Ibberson; Bernard Thorens (Elsevier, 2020)
Objectives: In the pathogenesis of type 2 diabetes, development of insulin resistance triggers an increase in pancreatic β-cell insulin secretion capacity and β-cell number. Failure of this compensatory mechanism is caused by a dedifferentiation of β-cells, which leads to insufficient insulin secretion and diabetic hyperglycemia. The β-cell factors that normally protect against dedifferentiation remain poorly defined. Here, through a systems biology approach, we identify the transcription factor Klf6 as a regulator of β-cell adaptation to metabolic stress. Methods: We used a β-cell specific Klf6 knockout mouse model to investigate whether Klf6 may be a potential regulator of β-cell adaptation to a metabolic stress. Results: We show that inactivation of Klf6 in β-cells blunts their proliferation induced by the insulin resistance of pregnancy, high-fat high-sucrose feeding, and insulin receptor antagonism. Transcriptomic analysis showed that Klf6 controls the expression of β-cell proliferation genes and, in the presence of insulin resistance, it prevents the down-expression of genes controlling mature β-cell identity and the induction of disallowed genes that impair insulin secretion. Its expression also limits the transdifferentiation of β-cells into α-cells. Conclusion: Our study identifies a new transcription factor that protects β-cells against dedifferentiation, and which may be targeted to prevent diabetes development. Keywords: Type 2 diabetes, Insulin resistance, β-Cell proliferation, Dedifferentiation, Transdifferentiation